2020
DOI: 10.4103/jehp.jehp_415_20
|View full text |Cite
|
Sign up to set email alerts
|

Psychological aspects of climate change risk perception: A content analysis in Iranian context

Abstract: BACKGROUND: Risk perception is an important predictor to mitigate climate change effects which can produce mental health consequences such as anxiety and depression. For developing policies of climate risk adaptation, awareness of public attitudes, beliefs, and perception is essential. At this study, researchers tried to focus on the often “unseen” psychological aspects of climate change. MATERIALS AND METHODS: A qualitative approach was done with a consistent content a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
(36 reference statements)
1
16
0
Order By: Relevance
“…In addition to the tangible mental health impacts related to exposure to specific climate change-related events, studies have reported psychological impacts of perceived risks associated with climate change [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the tangible mental health impacts related to exposure to specific climate change-related events, studies have reported psychological impacts of perceived risks associated with climate change [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The adaptation strategies against climate variabilities are a set of measures that are consciously used by people at the production and income unit level of rural households to mitigate the negative effects of climate change or even prevent its impacts. More specifically, investigating the awareness is assumed as a start point to make effective adaptation (Fosu-Mensah et al, 2012;Gandure et al, 2013;Yaro, 2013;Le Dang et al, 2014;Farrokhi et al, 2020;Mahmood et al, 2021). Since climate change management also needs some information about perceived risks (Gandure et al, 2013;Azadi et al, 2019a;Mahmood et al, 2021) and potential and inaction adaptation strategies (Smit and Wandel, 2006;Gandure et al, 2013;Dumenu and Obeng, 2016;Azadi et al, 2019a;Esfandiari et al, 2020;Mahmood et al, 2021) to attract required financial supports.…”
Section: Introductionmentioning
confidence: 99%
“…Studies addressing the issues of climate change awareness, perceptions, and adaptation in Iran (Zarafshani et al, 2005;Fatemi and Karami, 2010;Hayati et al, 2010;Keshavarz et al, 2013;e.g., Azizi Khalakhili and Zamani, 2014;Zobeidi et al, 2016;Azadi et al, 2019a,b;Jamshidi et al, 2019;Esfandiari et al, 2020;Farrokhi et al, 2020;Delfiyan et al, 2021;Ghazali et al, 2021) are basically focused on farmer groups. Therefore, exploiters of medicinal plants have not been studied so far.…”
Section: Introductionmentioning
confidence: 99%
“…This corroborates with Salehi et al (2016) that the global climate change knowledge showed that perception of climate change is sensible, and its awareness is influenced by societal and environmental factors. Farrokhi et al (2020) concurs that climate change perception is influenced by factors such as personal experiences, memories of climate events, and various biases. However, the most notable changes in climatic conditions understood by the local communities are in the form of erratic rainfall patterns resulting in drought, depleting water resources and while some areas are flooded.…”
Section: Introductionmentioning
confidence: 67%